2013
DOI: 10.1155/2013/958712
|View full text |Cite
|
Sign up to set email alerts
|

Photoinitiated Polymerization of 2-Hydroxyethyl Methacrylate by Riboflavin/Triethanolamine in Aqueous Solution: A Kinetic Study

Abstract: The polymerization of 1–3 M 2-hydroxyethyl methacrylate (HEMA) initiated by riboflavin/triethanolamine system has been studied in the pH range 6.0–9.0. An approximate measure of the kinetics of the reaction during the initial stages (~5% HEMA conversion) has been made to avoid the effect of any variations in the volume of the medium. The concentration of HEMA in polymerized solutions has been determined by a UV spectrophotometric method at 208 nm with a precision of ±3%. The initial rate of polymerization of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Here, we applied the endogenous, FDA-approved, non-toxic compound riboflavin in its water-soluble form flavin mononucleotide (FMN) as the photoinitiator for polymerization. Under UV and visible light, FMN was able to produce active radicals in the presence of the coinitiator triethanolamine (TEOHA) [31], which activates polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we applied the endogenous, FDA-approved, non-toxic compound riboflavin in its water-soluble form flavin mononucleotide (FMN) as the photoinitiator for polymerization. Under UV and visible light, FMN was able to produce active radicals in the presence of the coinitiator triethanolamine (TEOHA) [31], which activates polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…For example, DMPA, TPO, and I2959 are type I photoinitiators, and the mechanism of initiation is homolytic cleavage process and forms radicals upon exposure to light radiation which is a more direct and fast kinetic reaction. 5 According to the studies of Oster et al and Ahmad et al, 25,26 B2 combined with TEOA is a type II photoinitiator. TEOA is the co-initiator that provides electrons to Vitamin B2 and prompts the formation of TEOA radicals.…”
Section: Discussionmentioning
confidence: 99%
“…The RSD of the assay method is within ± 3%. The method has previously been used for the study of the photoinitiated polymerization of HEMA by RF/TEOHA system in aqueous solution [20].…”
Section: Measurement Of the Light Intensitymentioning
confidence: 99%
“…Polymerization reactions of HEMA in water at 1, 2, and 3 M concentrations in the presence of different photoinitiators have shown that the rates are decreased with an increase in the viscosity of the medium [20]. In order to confirm the effect of medium viscosity on the rate of these reactions, the values of 𝑘 obs in organic solvents in the presence of RF were plotted as a function of the inverse of solvent viscosity (Table 1) and a linear relationship was observed as expected (Figure 3).…”
Section: Riboflavin As Photoinitiatormentioning
confidence: 99%